MONEY POLITICS IN THE LEGISLATIVE ELECTION IN EASTLOMBOK PERIOD 2014-2019 (CASE STUDY IN SANDUBAYA - SITI NURUL ISNAINI WAHIDAH (The Scientia Journal of Social and Legal Studies, 2022)
Money politics is not a new thing in politic, it is existed since this country found; it is not an important thing to discuss. Money politics is not a grant and tithe as well as prize. It is a media to get or affect someone to give their vote in an lection. Besides, there are many kinds of money politic in Indonesia, even the candidates also concentrate to build personal team and winning the election trough patronage practices. Based on those problems, the present researcher stated the formulation problems as follows: how money politics is in the legislative election in East Lombok period 2014 in Sandubaya, Selong, East Lombok. ‘The method used was qualitative approach investigating descriptively. The data collections technique used were observation and interview to the society in Sandubaya; as the result the appropriate data were gained based on the reality. The conclusion of this research was: there were money politics in Sandubaya that was done by the legislative candidates as well as their successor team in an election, for example giving things, the building projects, and government pros. Those things were given to society for collecting vote from Sandubaya cociens.